Peningkatan Pendapatan Keluarga Melalui Manajemen Usaha Bandeng Cabut Duri - Rauly Sijabat; Ratih Hesty Utami Puspitasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The low level of public knowledge about fish processing causes fish to have less high economic value and less use as an alternative source of protein other than meat, significantly as an alternative solution to strengthen family income. Especially for milkfish, which has many thorns, causing people to be reluctant to consume and make processed milkfish a product of business choice. This phenomenon has led this service activity to introduce another alternative processing, namely thorn-pulled milkfish. Besides being comfortable, the tools used are relatively easy to get, and the price is not high. The processing of thorny milkfish can also be used as an alternative to increasing the economic value of milkfish, contributing to an increase in family income when engaged as a business route. The implementation of this thorn milkfish business management training activity showed that the participants had high enthusiasm. This was shown by the activity that the participants could independently remove or separate the milkfish from their spines. There is a growing desire to utilize thorns pulled milkfish as a source of family protein. Besides, the analysis of the thorn-pulled milkfish processing business also shows a potential opportunity as an alternative business in the context of strengthening the family economy.